Meningkatan Mutu Pendidikan melalui Penerapan Manajemen Berbasis Sekolah - Lisabe, Chandra Murdiono (Universitas Syiah Kuala, 2025)
Decentralization and democratization of education are less encouraged in Indonesia since national education management is still centralized throughout the country. Basically, problems with education management that have to do with how well resources are used. One clever tactic to combat the drawbacks of globalization is national education management. Strengthening it will therefore guide globalization in a way that is beneficial to the country's development. centralized educational administration system that has not been shown to significantly raise overall educational standards. Even in other instances, the centralized administration of education has resulted in a restriction of innovation across different educational levels and types.